Sociological Studies Minangkabau Traditional Mariage - Akhyar Hanif; Tri Yuliani; Riki Rikarno; Novi Budiman (Melayu Arts and Performance Journal, 2023)
Minang or Minangkabau is an ethnic cultural group that adheres to a distinctive customary system, namely a family system according to female lineage which is called the matrilineal system. In Minangkabau culture, marriage is one of the important events in the life cycle and is a very significant transitional period in forming a small group of new families to continue the lineage. For the Minangkabau people who are Muslim, marriages are carried out in accordance with the provisions of Law Number 1 of 1974 concerning Marriage. There are 2 (two) types of marriages for the Minangkabau indigenous people, namely: 1) Ideal marriage, namely marriage between close families such as children from nephews; 2) Abstinence marriage, namely marriage that cannot be carried out like the child of a mother or father. There are 2 (two) marriage procedures for the Minangkabau indigenous people, namely: 1) Marriage according to female relatives, namely the woman who is the initiator in marriage and in household life, from starting to find a mate to carrying out the marriage; 2) Marriage according to male relatives, namely the man who is the initiator in marriage and households, from starting to find a mate to carrying out the marriage and daily living expenses. The form of marriage in Minangkabau has changed according to the times. Previously, a husband meant nothing in the wife's family, now it is the husband who is responsible for his family